1993
DOI: 10.1152/jappl.1993.75.4.1630
|View full text |Cite
|
Sign up to set email alerts
|

Geometric hysteresis in pulmonary surface-to-volume ratio during tidal breathing

Abstract: We investigated the dynamic history dependence of lung surface area-to-volume ratio (S/V) during tidal breathing in live rabbits with use of our recently developed technique of diffuse optical scattering. We also examined the effect of methacholine (continuous intravenous infusion, 1-10 micrograms.kg-1.min-1) on lung micromechanics with the same technique. Animals were anesthetized, tracheostomized, and mechanically ventilated, and the left lung was exposed through a thoracotomy. An optical fiber delivering li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 0 publications
6
55
0
Order By: Relevance
“…This phase shift is also observed in the FSI simulation of the viscoelastic thin wall model for stenotic arteries performed by Chen [30]. The magnitude of the phase lag is about 10 degree which is validated by Miki et al [31].…”
Section: Resultssupporting
confidence: 73%
“…This phase shift is also observed in the FSI simulation of the viscoelastic thin wall model for stenotic arteries performed by Chen [30]. The magnitude of the phase lag is about 10 degree which is validated by Miki et al [31].…”
Section: Resultssupporting
confidence: 73%
“…Our laboratory has recently proposed two possible origins of "stretch-andfold" kinematics in the pulmonary acinus: first, that induced by a small departure (asynchrony) from kinematically reversible motion of alveolar walls (16,41), and, second, that due to the presence of saddle points associated with alveolar recirculation flows in the acinar flow field (40). With respect to the first mechanism, Miki et al (24) reported the presence of a small but consistent geometric hysteresis (i.e., temporal asynchrony) in lung expansion during normal tidal ventilation in live rabbits. By matching this degree of geometric hysteresis, we have generated physiologically realistic asynchrony in physical models (41) and computational models (16), which demonstrated that geometrical hysteresis, even if small, can produce stretchand-fold patterns and, consequently, induce substantial acinar flow irreversibility.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that, because of the peculiar geometry of the alveolated duct and its time-dependent motion associated with tidal breathing, under certain conditions, alveolar flow can be chaotic (16,40). As a consequence, acinar flow can be kinematically irreversible, even though it is a lowReynolds number viscous flow, and lung expansion and contraction are approximately self-similar and reversible (1,13,14,24,46). These findings are supported by a discovery in fluid mechanics that chaotic mixing can occur even in a viscous flow (2,25).…”
mentioning
confidence: 93%
“…To probe the role of the breathing pattern [tidal volume (V T ), breathing frequency (f)] on acinar airflow patterns, the model "breathed" in an expanding and contracting fashion, preserving geometric similarity. This assumption is based on experimental data (34,35). V T and f were adjusted (Table S1) to scale allometrically with body mass following the results in Fig.…”
Section: Methodsmentioning
confidence: 99%